How We Have Won the Battle and Lost the Peace: Women, Peace and Security Agenda Twenty Years - Antonijevic, Zorana (Journal of Regional Security, 2022)
The Resolution “Women, Peace and Security” unanimously adopted by the United Nations Security Council in 2000 fundamentally transformed discursive practices of gender equality into the fields of security, post-conflict reconstruction and peace. e twentieth anniversary was an opportunity to critically examine its impact on the gender mainstreaming of conflict, security and peace. This special issue contributes to the feminist security studies by discussing the shortcomings in the implementation of UNSCR 1325 from several research fields, including intersectionality and masculinity perspectives. After presenting the rationale and scope of the special issue, this article discusses the gender and security policy framing of the WPS Agenda, intending to conceptualise gender equality through three perspectives: the perspective of equal treatment, the women’s perspective, and the gender perspective. In conclusion, the article summarises the key contributions of this special issue and suggests some avenues for further research.